2011
DOI: 10.1021/nn103297e
|View full text |Cite
|
Sign up to set email alerts
|

Imine Derivatives on Au(111): Evidence for “Inverted” Thermal Isomerization

Abstract: Molecules that undergo reversible isomerization between trans and cis states, typically upon illumination with light at appropriate wavelengths, represent an important class of molecular switches. In this combined scanning tunneling microscopy (STM) and high-resolution electron energy loss spectroscopy (HREELS) study, we report on self-assembled arrays of imine derivatives on a Au(111) surface. Most of the molecules are found in the trans state after deposition at room temperature, but many of them change thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 46 publications
5
66
0
Order By: Relevance
“…6,7 This family of compounds have widely been studied because of their interesting physicochemical properties related to their structures, this fact, have made them the object of many theoretical and experimental investigations. [8][9] The most important features of the Schiff bases or their metal complexes it can be counted: their catalytic [10][11][12] and biological activities, [13][14][15] their application as metal ion sensors, 16-18 molecular disruptor [19][20][21][22] and also as anti-cancer agents, [23][24] among others.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This family of compounds have widely been studied because of their interesting physicochemical properties related to their structures, this fact, have made them the object of many theoretical and experimental investigations. [8][9] The most important features of the Schiff bases or their metal complexes it can be counted: their catalytic [10][11][12] and biological activities, [13][14][15] their application as metal ion sensors, 16-18 molecular disruptor [19][20][21][22] and also as anti-cancer agents, [23][24] among others.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the local concentration c of trans or cis isomers serves as morphological order parameter controlling the undulation of the surface. The tendency to form ordered islands with all molecules in the trans state has been experimentally proven by ultrahigh vacuum scanning tunneling microscopy for a monolayer of photochromic molecules on Au(111) (5). Furthermore, the electronic structure of the isomer is altered as the trans ⇀ cis photoisomerization causes an increase of the dipole moment from p trans = 0 Debye to p cis = 3 Debye (6,24) in combination with an increased electrical resistance of the isomer (4).…”
mentioning
confidence: 98%
“…Since the discovery of the unique photochemical properties of azobenzene in 1937 (1), azobenzenes have been mainly used in the chemical industry. Only recently, after studies of the molecular physics of the photoisomerization of azo dyes have revealed that the photoisomerization reaction occurs on the timescale of a few picoseconds (2,3), azobenzenes came back into focus as potential photoswitchable materials (4,5). Azobenzenes have been investigated in terms of ultrafast spectroscopy (4, 6, 7), mechanoisomerization (8), the effect of slow photons (9), two-photon absorption (10) and laser-induced periodic surface structuring (11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…By exchanging the azo with a C=N Figure 1. Chemical structures of the (a) para-TBA (2,2 ,5,5 -tetra-tert-butyl-azobenzene; studied in this work) and the (b) meta-TBA ( * studied previously [9,10] group, and thus moving to imine derivatives, a quite different isomerization behavior was observed [19]. Note that the concept of trans-cis isomerization has recently been applied to molecular machines that are driven by such a chemical process [20,21].…”
mentioning
confidence: 86%